Oxime ligands: organometallic synthesis and catalysis - Iyer, Suresh (SYNTHETIC COMMUNICATIONS, 2024)
Ligands are at the heart of coordination chemistry. They conjure the magic of transition metals expressed in organometallic catalysis. Phosphine or P-ligands have found vast utility in transition metal chemistry, though demanding tedious synthesis. Several N, S-based ligands also find application in organometallic chemistry. Oximes are easily derived from aldehydes and ketones by simple reactions with hydroxylamine. Thus, an extensive library of oximes is available with different structural and electronic variations essential for coordination chemistry and catalysis. Several compounds with complex structural features, unavailable for phosphorous ligands, can be readily converted into active oxime ligands in a single derivatization step. Oxime ligands and metal complexes are applied in synthesizing diverse organic molecules and thus versatile ligands in organotransition metal chemistry.
Keywords: cobaloxime; Cross-coupling; oxime palladacycles; oximes; radical cyclization